2018
DOI: 10.1037/lhb0000311
|View full text |Cite
|
Sign up to set email alerts
|

The impact of victimization and mental health symptoms on recidivism for early system-involved juvenile offenders.

Abstract: Although research has linked mental health symptoms and prior victimization to recidivism for youth on probation or in detention, little attention has been given to these risk factors for early system-involved youth. We conducted a survival/hazard model to estimate the impact of official records of abuse/neglect, crime victimization, and mental health issues (mood, anxiety, disruptive, and substance use disorders) on recidivism in a sample of 2,792 youth in a large Midwestern diversion program. Results indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…The importance of the present study is clear-mental health complications as a result of stigmatization within the community increase the vulnerability of ex-convicts to commit crime and thereby escalate a country's recidivism rates (Wylie & Rufino, 2018). The current study will therefore attempt to achieve the following:…”
Section: The Current Studymentioning
confidence: 99%
“…The importance of the present study is clear-mental health complications as a result of stigmatization within the community increase the vulnerability of ex-convicts to commit crime and thereby escalate a country's recidivism rates (Wylie & Rufino, 2018). The current study will therefore attempt to achieve the following:…”
Section: The Current Studymentioning
confidence: 99%
“…This means that there could be a great variety among adolescents whose trauma diagnosis is based on developmental trauma such as child abuse or neglect, compared to those who have a history of severe accidents, for example. When studying recidivism in a large sample of juvenile offenders (n=2792), Wylie and Rufino 22 found that adolescents with official records of certain kind of victimisation experiences such as abuse/neglect and personal crime victimisation were more likely to recidivate sooner than those without these victimisation experiences. Also, when examining the risk of self-harm and violent criminality among adolescents and young adults following injuries or poisonings during their childhood, Webb et al 23 found that the highest absolute risk was observed for violent offending among men admitted to hospital for interpersonal violence and for self-harm among women admitted to hospital following self-harm.…”
Section: Discussionmentioning
confidence: 99%
“…For example, unresolved trauma can affect youth by creating mental health issues or behavioural problems, showing how the environment can impact individual issues. Wylie and Rufino (2018) found that 90 percent of youth who reported victimization also experienced trauma, which then led to emotional and behavioural problems (p. 559). This can mean directing internalized rage and pain at other people, which can result in victims acting out in violent, and possible criminal, ways because of the trauma they have not dealt with.…”
Section: Interactions Between Individual and Social Factorsmentioning
confidence: 99%
“…Being a victim can negatively impact a young person's life experiences. Victimization may include being a victim of crime, as well as experiencing maltreatment and adverse childhood experiences (Wylie & Rufino, 2018). In addition to being a victim of crime, being the offender, or the person who causes harm, can also affect youth, as being involved with crime impacts their decisions to participate in other risky behaviours like being involved with drugs and alcohol, socializing with deviant or dangerous individuals, behaviors that contribute to injuries and violence, tobacco use, and truancy.…”
Section: Introductionmentioning
confidence: 99%